2016
DOI: 10.1089/jmf.2016.0072
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different High-Protein Low-Carbohydrates Proprietary Foods on Blood Sugar in Healthy Subjects

Abstract: The aim of our work was to analyze the effects on blood sugar through the calculation of the glycemic score (GS) of 10 different high-protein-low-carbohydrates proprietary foods which are commonly used as meals during very low carbohydrate ketogenic diet or during low carbohydrate diet. 14 healthy female tested the glycemic response curve elicited by 1000 Kj of glucose three times within 3 weeks period (1 test each week) compared to each of the 10 test-foods once on separate days twice a week. After determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…KD effect on insulin and glycemic control deserves mention. Several researches have demonstrated that KD can reduce glucose and insulin concentration in obese, insulin resistant individuals and diabetics [72][73][74][75]. This effect is not only related to a reduced intake of glucose within the diet, but also to the improvement in insulin sensitivity [12].…”
Section: Discussionmentioning
confidence: 99%
“…KD effect on insulin and glycemic control deserves mention. Several researches have demonstrated that KD can reduce glucose and insulin concentration in obese, insulin resistant individuals and diabetics [72][73][74][75]. This effect is not only related to a reduced intake of glucose within the diet, but also to the improvement in insulin sensitivity [12].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subjects daily consumed four food supplements and liquid herbal extracts. Food supplements are high proteins (19 g/portion) and very low carbohydrate (3.5 g/portion) formulas simulating the aspect and taste of common carbohydrate rich foods added with dry phytoextracts [43]. Liquid herbal extracts were used for their draining/toning activity, useful to Table 3.…”
Section: Dietmentioning
confidence: 99%
“…A nutritional protocol as the KD may be hard to be maintained for long periods due to the lack of sweet taste [25], thus, for this reason, in the last years, many ready-to-eat ketogenic products (RKP) have been created [26] in addition to usual low carbohydrate foods [27]. In our protocol we used some RKP as a ketogenic pasta (selected with a ketogenic ratio of fats: protein+carbohydrate equal to 4:1) (Le Gamberi Foods, Forlì, Italy), and other RKP (specialty meals and drinks) that mimics the taste of carbohydrates [27], constituted principally of high-quality protein (18 g of protein per portion), fibers, and electrolytes (mainly magnesium and potassium) [28] (Tisanoreica® by Gianluca Mech S.p.A., Asigliano Veneto, Vicenza, Italy). It has been demonstrated that the use of RKP increases the adherence to the ketogenic nutritional protocol [25,29,30].…”
Section: Dietary Interventionmentioning
confidence: 99%